APPROACHES AND ISSUES IN TEACHING SPEAKING FOR ENGLISH AS A FOREIGN LANGUAGES - Abdurahmonov, Komiljon (Educational Research in Universal Sciences, 2023)
English teachers as a foreign language is a challenging task. This study attempted to investigate English teaching challenges as well as the solution taken by the English as a foreign teachers. The article deals with the English teachers’ point of view in facing teaching chllanges in the classroom and the solution they implemented to solve them through interview. A number of challenges emerged, partly coming from students, partly from teachers, and partly from the school’s facility. Students are challenged by their lack of vocabulary mastery, low concentration, lack of discipline, boredom, and speaking problem. Meanwhile, teachers’ challenges are shortage of teachers’ limited mastery of teaching methods and lack of professional development. In addition, facilities issues including inadequate resources and facilities, and time constraint. The solutions to overcome these challenges were also suggested in this article.